IgA Targeting Human Immunodeficiency Virus-1 Envelope gp41 Triggers Antibody-Dependent Cellular Cytotoxicity Cross-Clade and Cooperates with gp41-Specific IgG to Increase Cell Lysis - Duchemin, Maxence; Khamassi, Marwa; Xu, Lin; Tudor, Daniela; Bomsel, Morgane (Frontiers in Immunology, 2018)
The protective efficacy of human immunodeficiency virus-1 (HIV-1) antibodies (Abs) remains mostly correlated with their in vitro neutralizing activity engaging their Fab region. However, anti-HIV-1 Abs also mediate a broad array of Fc-mediated effector functions including Ab-dependent cellular cytotoxicity (ADCC), which depend primarily on the Ab isotype. While ADCC is commonly associated with HIV-1 gp120 envelope-specific IgGs, whether IgAs, especially those targeting the HIV-1 gp41 envelope, also mediate ADCC remains elusive. Therefore, to assess the capacity of IgA specific for HIV-1 to induce Fcα-mediated ADCC, we used the gp41 envelope-specific IgA transformed from the broadly neutralizing 2F5-IgG we have previously reported to induce ADCC. We demonstrate that 2F5-IgA engages FcαRI (CD89), expressed on human monocytes used as effector cells, to induce the lysis of HIV-1 Clade A- and B-infected target cells by ADCC. Furthermore, the 2F5-IgA and 2F5-IgG cooperate to enhance target cells lysis by ADCC. Cooperation in ADCC is also observed between 2F5-IgA and the broadly neutralizing 10E8-IgG. These results provide a new perspective for IgA in protection against HIV-1 acquisition or reservoir eradication and suggest that inducing IgA by vaccination, in particular when targeting gp41, in combination with IgG could strengthen protection by complementary and cooperative activities with IgG.